The Gradual Shift of Overweight, Obesity, and Abdominal Obesity Towards the Poor in a Multi-ethnic Developing Country: Findings From the Malaysian National Health and Morbidity Surveys - Mariapun, Jeevitha; Ng, Chiu Wan; Hairi, Noran Naqiah (Japan Epidemiological Association, 2018)
Background: Economic development is known to shift the distribution of obesity from the socioeconomically more advantaged to the less advantaged. We assessed the socioeconomic trends in overweight, obesity, and abdominal obesity across a period of significant economic growth. Methods: We used the Malaysian National Health and Morbidity Survey data sets for the years 1996, 2006, and 2011 to analyze the trends among adults aged 30 years and above. The World Health Organization’s Asian body mass index cut-off points of ≥23.0 kg=m 2 and ≥27.5 kg=m 2 were used to define overweight and obesity, respectively. Abdominal obesity was defined as having a waist circumference of ≥90 cm for men and ≥80 cm for women. Household per-capita income was used as a measure of socioeconomic position. As a summary measure of inequality, we computed the concentration index. Results: Women in Peninsular Malaysia demonstrated patterns that were similar to that of developed countries in which the distributions for overweight, obesity, and abdominal obesity became concentrated among the poor. For women in East Malaysia, distributions became neither concentrated among the rich nor poor, while distributions for men were still concentrated among the rich. Chinese women, particularly from the richest quintile, had the lowest rates and lowest increase in overweight and obesity. All distributions of Chinese women were concentrated among the poor. The distributions of Malay men were still concentrated among the rich, while distributions for Chinese and Indian men and Malay and Indian women were neither concentrated among the rich nor poor. Conclusion: As the country continues to progress, increasing risks of overweight and obesity among the socioeconomically less advantaged is expected.